THE ECONOMICS OF LUCKINESS: HOW CRAZY ARE MALAYSIAN CHINESE TOWARDS CAR PLATE NUMBER â€œ8â€? (Malaysian Management Journal, 2017)
The Chinese society is well-known for its obsession towards number â€œ8â€. Eight is the luckiest number to the Chinese as its pronunciation resembles the meaning of prosperity, wealth or fortune. Prior research estimating the marginal effect of â€œ8â€ on winning bid prices of car plate numbers attributes the positive impact of â€œ8â€ on bid prices to superstitious value. However, the estimated positive effect could also be attributed to Veblen goods and future resale consideration. Thus, an upward bias might exist in prior researchâ€™s estimation. This study aimed to circumvent this issue by comparing the marginal effect of all â€œ8â€ car plate numbers of Malaysian Chinese bidders and their non-Chinese counterparts who are neutral towards number â€œ8â€. Descriptive statistics results reveal that the majority of all â€œ8â€ plates are won by Chinese bidders. However, regression results reveal that Chinese bidders have a lower estimated marginal effect of number eight than their non-Chinese counterparts. This implies that while number â€œ8â€ is popular among the Chinese, this popularity does not translate into higher bidding prices. These findings suggest the roles of Veblen goods and future resale consideration should not be ignored in estimating the superstitious value in car plate numbers.